Surfing, windsurfing, snowboarding, and skateboarding: medical aspects of board sports - van Tilburg, C. (The Physician and Sportsmedicine, 1996)
With the rise in popularity of board sports, primary care physicians need to understand the injury risks and environmental hazards faced by surfers, windsurfers, snow-boarders, and skateboarders. Physicians can play an important role by telling patients about injury prevention strategies, including using proper equipment, wearing protective gear, taking lessons, and riding in terrain and weather conditions appropriate for one's skill level.